AB0759 The assessment of gastrointestinal tract involvement through ucla sctc git 2.0 questionnaire identifies scleroderma patients with reduced bone mineral density. (12th June 2018) - Natalello, G.; De Lorenzis, E.; Canestrari, G.B.; Gigante, L.; Verardi, L.; Mirone, L.; Bosello, S.L.; Ferraccioli, G.; Gremese, E.
Abstract : Background: Gastrointestinal (GI) symptoms are seen in majority of patients with Systemic Sclerosis (SSc) and are a common presenting feature of disease. Severe GI involvement may lead to malabsorption which represents a poor prognostic factor. Accordingly, a regular monitoring of gastrointestinal tract involvement and nutritional status appears crucial in SSc patients. Previous studies reported low values of bone mass density (BMD) in SSc patients 1 . While no specific relationship has emerged between the two conditions, it's likely that disease related GI involvement may contribute to the alterations in BMD. Objectives: To determine if GI-related clinical status was associated to low bone density in our cohort of SSc patients. Methods: Two-hundred-ten unselected SSc patients have been enrolled. The 7-items UCLA SCTC GIT 2.0 questionnaire and Malnutrition Universal Screening Tool (MUST) were administered to each patient. A comprehensive medical history was collected. A blood panel for nutritional status was also performed. T-scores and Z-scores at lumbar spine, femoral neck, Ward's and total hip measured by dual-energy X-ray absorptiometry (GE Lunar Prodigy) were measured. Results: In our cohort, 86.7% of patients reported some GI symptoms. The mean UCLA GIT total score was 0.345±0.34 and 51 patients (24.3%) were at risk of malnutrition according to MUST (score ≥1). 53.7% patients had BMD values<1, and 12.5% had BMD values≤−2.5 at any of the considered sections. Patients with reduced BMD (<-1) showed similar levels of selected nutritional blood markers compared to subjects with normal BMD, including vitamin D and albumin. Patients with spine T-score <-1 had lower BMI (23.2±3.9 vs 25.2±4.8; p=0.011) and reported higher UCLA GIT reflux (0.66±0.63 vs 0.42±0.48; p=0.016), distention (0.80±0.72 vs 0.53±0.56; p=0.15) and total score (0.42+0.37 vs 0.27±0.30; p=0.006) compared to patients with normal BMD. Similar significant differences were observed in the same domains for patients with total hip T-score values <-1. Femoral neck T-score <−2.5 was associated with higher UCLA GIT reflux (0.88±0.78 vs 0.48±0.50; p=0.022), soilage (0.50±0.78 vs 0.14±0.52; p=0.041) and total score (0.50±0.37 vs 0.31±0.33; p=0.012). On the other hand, the comparison of patients with severe, moderate and mild symptoms according to UCLA GIT total score 2 showed an association between progressively lower values of spine and total hip T-score and increasing severity of GI symptoms (ANOVA for spine T-score: p=0.015; for total hip T-score: p=0.048). Patients at risk of malnutrition (MUST score ≥1) presented significant lower T-score for all the considered sections (spine and hip) and significant lower total hip Z-score. Conclusions: In our SSc cohort gastrointestinal symptoms were frequent and were associated with low BMD. Considering the heterogeneity of GI involvement, UCLA SCTC GIT 2.0 emerged as a useful and feasible tool to assess GI involvement and other associated comorbidities. In particular, SSc patients who report remarkable GI symptoms and are at risk of malnutrition according to MUST may benefit from a stricter control of BMD to promptly detect osteopenia and osteoporosis. References: [1] Omair MA, et al. J Rheumatol. 2013 [2] Khanna D, et al. Curr Opin Rheumatol. 2013 Disclosure of Interest: None declared